2001
DOI: 10.1207/s15324826an0802_2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Dysfunction, Mood Disturbance, and Emotional Status of Munitions Workers

Abstract: The objective of this study was to compare the neuropsychological function, emotional status, visual function, and illness prevalence of 265 former munitions plant workers (M age = 56.7 years, M years of education = 12.07; 201 African American, 64 White) exposed to organic solvents for an average of 17.03 years with that of a group of 77 unexposed controls (M age = 51.3 years, M years of education = 13.07; 30 African American, 47 White). Neuropsychological tests were selected from the World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Moreover, the finger-tapping test is widely used to evaluate motor function in the upper limbs (6-8) and the relationship between hand preference and hand skill (9) in healthy individuals and to assess hand skill and coordination (10-12) for occupations in which the hands are essential. The finger-tapping test is also used for psychomotor evaluations (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Moreover, the finger-tapping test is widely used to evaluate motor function in the upper limbs (6-8) and the relationship between hand preference and hand skill (9) in healthy individuals and to assess hand skill and coordination (10-12) for occupations in which the hands are essential. The finger-tapping test is also used for psychomotor evaluations (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Significantly lower finger-tapping scores have been reported in several exposure studies (13,14,16,17,20). However, significantly higher scores have also been reported (18). Moreover, finger-tapping performance scores were better in males compared with females (12).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have mainly reported the total number of tappings in a certain test period (13)(14)(15)(16)(17)(18)(19)(20)23) and the tapping speed (6,25). Kauranen et al (25) compared patients with rheumatoid arthritis (RA) to healthy individuals and found no significant differences in the finger-tapping values of the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations